Assessing depression in a geriatric cancer population. Issue 10 (16th May 2016) - Saracino, Rebecca M.; Weinberger, Mark I.; Roth, Andrew J.; Hurria, Arti; Nelson, Christian J.
Abstract: Objective: To examine the ability of three popular self‐report measures of depression to assess depression in a geriatric cancer setting. Method: Cancer patients 70 years or older and on active treatment completed the Geriatric Depression Scale‐Short Form, the Hospital Anxiety and Depression Scale, and the Center for Epidemiological Studies Depression Scale—Revised, and were interviewed using the depression module of the Structured Clinical Interview for DSM disorders (SCID) as the 'gold standard.' Analyses included calculating internal consistency, ROC curves, and the sensitivity and specificity to detect major depression (MDD) or minor depression (i.e. subthreshold depression). Results: In a sample of 201 cancer patients (85% White; 64% completed college degree or higher), all three of the self‐report measures produced adequate internal consistency and predicted depression greater than chance. However, the published cutoff scores for detecting MDD produced inadequate sensitivity, suggesting these scores will miss as many as 33%–83% of geriatric cancer patients who are depressed. Revised cutoff scores were lower than published cutoff scores. Conclusion: Although these measures produced good internal consistency and were better than chance at predicting depression in a geriatric cancer sample, the published cutoff scores for these measures did not perform well in predicting MDD nor minor depression. Of the three measures, the CES‐D appeared to have the most utility. This data suggests that these popular screening measures may be inadequate for reliably identifying depression in a geriatric cancer population. Researchers and clinicians, therefore, should use caution when selecting depression measures for geriatric cancer patients and consider using the lower cut‐off scores presented here.